Pengaruh Penjualan Bersih dan Total Utang terhadap Laba Bersih: Studi Kasus pada PT. Kalbe Farma Tbk Periode 2014-2023 - Eza Rizki Prasetia; Palupi Permata Rahmi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study aims to determine whether there is an influence of net sales and total debt on net profit at PT. Kalbe Farma Tbk for the 2014-2023 period, both partially and simultaneously. The type of research used in this study is associative research with a quantitative approach. The data collection technique employed is documentation. The sampling technique used in this study is purposive sampling. The sample in this study is the financial report data of PT. Kalbe Farma Tbk for the 2014-2023 period. The independent variables in this study are net sales and total debt. The dependent variable is net profit. The results of this study are: (1) partially, net sales do not have a significant effect on net profit at PT. Kalbe Farma Tbk for the 2014-2023 period; (2) partially, total debt has a significant effect on net profit at PT. Kalbe Farma Tbk for the 2014-2023 period; and (3) simultaneously, net sales and total debt affect net profit by 86,2%, while the remaining 13,8% is influenced by other factors. The results of this study confirm that net sales are a key factor in determining the company’s net profit, while total debt does not have a significant individual impact. Based on these results, it is recommended that the company continue to improve its net sales and properly manage its debt to maintain a positive impact on its financial performance.